2014
DOI: 10.1155/2014/863404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacancy Cluster Defects on Electrical and Thermodynamic Properties of Silicon Crystals

Abstract: A first-principle plane-wave pseudopotential method based on the density function theory (DFT) was employed to investigate the effects of vacancy cluster (VC) defects on the band structure and thermoelectric properties of silicon (Si) crystals. Simulation results showed that various VC defects changed the energy band and localized electron density distribution of Si crystals and caused the band gap to decrease with increasing VC size. The results can be ascribed to the formation of a defect level produced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This ease of thermally activated electrical conduction in GLAD Si films prepared with the most glancing angles is related to structural defects induced by the oblique angle deposition process, and also impurities such as oxygen incorporated in the porous structure intrinsic to the tilted columnar architecture. It has been previously reported that defects [15] as well as oxygen atoms [16] in Si material both reduce the energy gap. Since the GLAD process particularly produces growing defects and a porous columnar structure at high deposition angles ( > 70°), they contribute to decrease the activation energy.…”
Section: Resultsmentioning
confidence: 99%
“…This ease of thermally activated electrical conduction in GLAD Si films prepared with the most glancing angles is related to structural defects induced by the oblique angle deposition process, and also impurities such as oxygen incorporated in the porous structure intrinsic to the tilted columnar architecture. It has been previously reported that defects [15] as well as oxygen atoms [16] in Si material both reduce the energy gap. Since the GLAD process particularly produces growing defects and a porous columnar structure at high deposition angles ( > 70°), they contribute to decrease the activation energy.…”
Section: Resultsmentioning
confidence: 99%
“…Meyer et al studied the PME in a small thin ringlike mesoscopic superconductor, the region of PME is above the transition between states of the different angular moments and is well known, this phenomenon is a manifestation of the decreasing energy as the magnetic field is increasing [18]. Palacios et al explain the PME as a result of the metastability of the vorticity [19]. For high vorticity states, the heat capacity presents a peak whose position with the change in the field is related to the paramagnetic Meiss effect and can lead to an observation of positive magnetization [12].…”
Section: Introductionmentioning
confidence: 99%
“…For high vorticity states, the heat capacity presents a peak whose position with the change in the field is related to the paramagnetic Meiss effect and can lead to an observation of positive magnetization [12]. Huang et al [20] studied the effects of vacancy cluster defect in the entropy, enthalpy, free energy and heat capacity of silicon crystals, they found that the heat capacity decreases as the vacancy cluster defect size increased. Analytic calculation and a model that describes the low-temperature heat capacity of in-homogeneous cuprates compounds was performed in a mesoscopic disordered s-wave superconductor and the results reproduce the features of the heat capacity for MgB 2 [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This is done by creating a supersaturation of vacancy-defects (V) in the Si film via self-implantation and rapid-thermal annealing. Experiments attempt to replicate theoretical studies, which have predicted that large V concentrations (~10 21 cm -3 ) have a significant impact on Si, reducing κ by up to 95 % at 300 K [6][7][8] as a result of increased phonon scattering and reduced mean-free-path length for phonons. Because the equilibrium concentration of Vs is extremely low in regular Czochralski-grown Si (<10 11 cm -3 [9]), self-implantation of Si ions is used to introduce high V concentrations in the near-surface of Si thin-films.…”
Section: Introductionmentioning
confidence: 99%